High performance fibre reinforced concrete (HPFRC) in tropical climate condition - Saad, Siti Asmahani; Mohamed Osman, Mariana (IIUM Press, International Islamic University Malaysia, 2017)
Additional of fibre in concrete creates fibre reinforced concrete (FRC) with an improvement of the mechanical properties of the concrete. However, additional of fibres in FRC has limited to 2% to allow normal mixing procedure. To address this issue, high performance fibre reinforced concrete (HPFRC) which is relatively new in construction industry is studied. Since very limited information on its capacity in tropical climate condition exposure, this project focuses on investigation of HPFRC compressive strength and microstructure properties in tropical climate condition. Grade 80 cement slurry is used with 3%, 4% and 5% hooked-end steel fibre to produce HPFRC. Total numbers of 56 samples which are divided into 4 sets and exposed to two different curing methods namely water curing method and steam curing method at 80oC. Out of the 4 sets, 2 sets are exposed to tropical climate condition using climatic chamber at 80% relative humidity (RH) and constant temperature of 35oC for 30 days. Compression and ultrasonic pulse velocity (UPV) tests are carried out at 28 days to identify the strength of HPFRC. Scanning electron microscopy (SEM) analysis is done to ascertain the microstructure properties of HPFRC. The highest compressive strength of 152.2 MPa was recorded for steam curing samples after exposed to tropical climate condition for 30 days with 5% steel fibre volume. The regression analysis developed exponential and polynomial expressions to correlate the pulse velocity values with the compressive strength. The best fit correlation value (R2) showing the significant relation of the two tests is recorded as 0.7976.